SLEEP APNEA SYNDROME IN RHEUMATOID ARTHRITIS PATIENTS WITH UPPER CERVICAL LESIONS - TAKEI Mitsuhiko (Journal of The Showa Medical Association, 1997)
Lesions of the cervical spine often appear in rheumatoid arthritis (RA) and may result in sudden death owing to compression of the medulla oblongata and the spinal cord due to subluxation of the upper cervical spine. Recent research in sudden death has focused on sleep apnea syndrome (SAS) ; however, few reports address the effects of complications of SAS in RA. To investigate factors in the occurrence of SAS in RA, we studied findings obtained on polygraphy during sleep, radiography of the cervical spine, and magnetic resonance imaging (MRI) . Subjects were 7 RA patients (imen, 6 women) : 5 cases were stage IlI, 2 cases were stage N, 1 case was class 2, and 6 cases were class 3. We diagnosed SAS when apnea occured more than five times in 1 hour. Three cases were diagnosed as SAS: 1 case was caused by anterior subluxation and 1 case was caused by both anterior and vertical subluxation. In each case compression of the ventral part of the lower medulla was found on MRI. Another case showed the secondary symptom of micrognathia caused by destruction of the mandibular joint. Sleep apnea was not observed in patients who had no compression of the ventral part of the lower medulla. It has been suggested that a respiratory rhythm generator is present in the ventral part of the lower medulla; therefore, the compression of the ventral part of the lower medulla observed on MRI is one of the factors in SAS regardless of the direction of subluxation. 慢性関節リウマチにおいて上位頚椎病変を合併することは少なくなく, 上位頚椎の亜脱臼による延髄及び脊髄の圧迫で急速な死の転帰をとることがある.突然死の原因として近年睡眠時無呼吸症候群 (Sleep apnea syndrome; 以下SAS) が注目されているが, RAにおけるSASの合併に関する報告は少ない.本研究では上位頚椎病変を有するRA患者に睡眠ポリグラフィー, 頚椎単純X線撮影及びMRIを施行し画像診断上の特徴よりSAS出現の危険因子を明らかにした.対象はRA患者7例で男性1例女性6例, 年齢は42歳から60歳, stage III: 5例, stageIV: 2例, class2: 1例, class3: 6例であった.1時間あたりの無呼吸回数 (apnea index) が5以上のものをSASとした.画像診断としてはatlanto-dental interva1 (ADI) , 残余脊柱管前後径 (space available for the cord; 以下SAC) , Perpendicular distance; 以下PD) , Redlund-Johnell値及rama1-height値を計測, MRIでは特に延髄腹側の状態を観察した.SASと診断された症例は3例で前方亜脱臼, 及び前方亜脱臼と垂直脱臼の合併が各1例ずつでいずれもMRIで延髄下部腹側の圧迫が認められた.また1例は顎関節破壊による2次性の小顎症を呈していた.延髄下部腹側の圧迫の認められない症例ではslee papneaは出現していなかった.前方亜脱臼を呈する患者ではSACが13mm以下, 垂直亜脱臼を呈する患者ではPDが7mm以下となり, MRI画像で肉芽などによる延髄下部, 上位頚髄の特に腹側の圧迫像が見られる場合にはSASを起こしている可能性が高かった.延髄下部腹側には呼吸リズム産生機構があることが示唆され, 亜脱臼の方向にかかわらずMRIでの延髄下部腹側の圧迫像の存在はSAS発症の危険因子と考えられた.